Determination of the Trophic Level of Almus Dam Lake and Research its Phosphorus Carrying Capacity - Polat, Fatih; Ozmen, Habibe (Foundation Environmental Protection & Research-Fepr, 2011)
Total phosphorus and Secchi disk visibility parameters of Almus Dam Lake located in the district Almus of province Tokat were seasonally determined at nine stations located along the lake. Trophic status of Almus Dam Lake were determined by comparing the results of our measured parameters with the values of OECD. In the second phase of the research, phosphorus carrying capacity were determined using Beveridge suggested phosphorus loading model recognized by OECD. Phosphorus carrying capacity of the Lake was determined as 2275.21 mg.m(-2).year(-1). It has been concluded that the lake will renew itself without going to eutrophication when the total production of aquaculture is between 4023.33 (Food Conservation Ratio (FCR):1.5-1) and 6981.76 (FCR: 1:1).
Almus baraj gölünde trofik seviyenin belirlenmesi ve gölün fosfor taşıma kapasitesinin araştırılması
Keywords: Almus Dam Lake; Phosphrus Carrying Capacity; Trophic Status